THE IMPACT OF TECHNOLOGY ON SCIENCE FICTION TRANSLATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The advent of digital technology has fundamentally transformed the translation of science fiction literature. Tools such as computer-assisted translation (CAT) software, machine translation, and collaborative online platforms have reshaped how translators approach complex scientific terminology, neologisms, and culturally specific references. This article examines the ways in which technology influences translation strategies, improves accuracy, and enhances accessibility for global audiences. By analyzing key examples, the study demonstrates that technology not only accelerates the translation process but also affects stylistic fidelity, reader engagement, and the international dissemination of science fiction.